Immunogenicity of primary and booster MenACWY-TT vaccination in older adults and the importance of IgM - M. Visser; D. M. van Rooijen; J. Wolf; L. Beckers; M. Ohm; M. I. de Jonge; A. M. Buisman; G. den Hartog (npj Vaccines)
Abstract Adults aged 65 years and older are at increased risk for infectious diseases, including invasive meningococcal disease (IMD), yet data on meningococcal vaccine immunogenicity in this population remain limited. In this randomized clinical trial (CTIS: 2024-513640-29-00, 13-05-2024), 222 older adults (65–85 years) received a quadrivalent meningococcal conjugate vaccine (MenACWY-TT), with 104 adults receiving a booster dose one year later. Serum bactericidal activity (rSBA) and polysaccharide-specific IgG and IgM concentrations were assessed. One month post-primary vaccination, 91–98% of participants had protective rSBA titers (≥8). Booster vaccination transiently increased bactericidal responses, but titers returned to pre-booster values within a year for MenC, -W, and -Y. rSBA titers correlated stronger with IgM than IgG, particularly for MenW and -Y. Interestingly, IgM depletion markedly reduced rSBA titers, while IgG depletion had minimal impact. These findings highlight that MenACWY-TT vaccination elicits functional antibody responses in older adults, largely driven by IgM.